THE RELATIONSHIP BETWEEN PERCEPTION OF SUSCEPTIBILITY AND SERIOUSNESS OF DISEASE WITH INDIVIDUALS’ ADEQUACY WATER INTAKE IN SOUTHEAST SULAWESI: Water intake and perception - Tasnim, Tasnim; Saafi, La Ode; Munir, Sanihu; Karuniawati, Kadek Ayu; Fitri, Fitri; Tias, Nuzul Wahyuning; Handayani, Ririn Putri; Indriani, Indriani; Sari, Eka Putri; Saripati, Wa Ode Fitra (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: The majority of people in Southeast Sulawesi had higher prevalence of cardiovascular diseases such as hypertension. One of the problems was they had insufficient water consumption. The individuals’ perception of vulnerability and seriousness of the disease were assumed to be causes of this condition.  Therefore, this study aims to analyze the relationship and influence of perceived vulnerability and perceived seriousness of disease on the level of adequate water intake in Kendari City and Konawe Regency. Methods: This research recruited 200 respondents Southeast Sulawesi, especially in Nambo District, Kendari City and Morosi District, Konawe Regency, in May-June 2024. The study used a cross-sectional study. The independent variables are perception of vulnerability and seriousness of the disease. Meanwhile, the dependent variable is adequate daily water intake. Data analysis used the chi-square and liner regression tests Results: The results showed that perceived vulnerability was related and had a significant effect on adequate water intake (p value=0.038<0.05). Meanwhile, the perception of the seriousness of the disease was not significantly related to the adequacy of daily water intake (p value=0.592>0.05). Conclusion: This research can be concluded that awareness of the level of self-vulnerability encourages individuals to take corrective actions, one of which is by consuming water according to recommendations, namely at least 2 litters a day. On the other hand, there is no difference between individuals who have or have not felt the severity of their illness. which is significant in consuming water a day.